2022
DOI: 10.3390/su14127162
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Nature, Financial Technology, and Corporate Innovation in China

Abstract: Corporate innovation has become the main driving force for the long-term development of enterprises, but the characteristics of high risk, long cycle, and high capital demand of corporate innovation activities expose enterprises to high financial rejection. Financial technology, formed by combining digital technology with traditional financial services, is gradually changing the financial service model and providing new ideas for corporate investment and financing. In this study, using the data of non-financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Bettinger (1972) originally proposed that financial technology is the combination of commercial banking knowledge, modern management techniques and computers, which represents the integration of finance and technology. The biggest difference between financial technology and traditional finance is ‘technologisation’ (Gao & Jin, 2022). The financial services provided by financial technology combine a variety of emerging technologies, such as big data, cloud computing, artificial intelligence, blockchain and so on.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Bettinger (1972) originally proposed that financial technology is the combination of commercial banking knowledge, modern management techniques and computers, which represents the integration of finance and technology. The biggest difference between financial technology and traditional finance is ‘technologisation’ (Gao & Jin, 2022). The financial services provided by financial technology combine a variety of emerging technologies, such as big data, cloud computing, artificial intelligence, blockchain and so on.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Considering the omitted variables and endogeneity issues that bring bias to the results of this study, this study refers to Gao and Jin (2022). It chooses financial technology lagged one period (LFintechi) as the instrumental variable and uses the 2SLS method to perform robustness tests.…”
Section: Positive Analysismentioning
confidence: 99%
“…The coexistence of high risk and high profit makes it particularly important for enterprises to make decisions about innovation. Gao et al [ 6 ] found that the problem between the large amount of R&D funding required by enterprises and traditional forms of finance has long been an obstacle to innovation. Williams [ 7 ] discovered that the digital economy has solved the financing problem of enterprises with its unique advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The existing research shows that fintech development can strengthen banks' risk control ability [11][12][13][14], improve commercial banks' efficiency [15,16] and promote competition between banks [17] through "enabling", thus forcing commercial banks to make digital transformations and change the traditional financial service mode. At the same time, fintech development can effectively ease corporate financing constraints [18] and promote entrepreneurship [19], innovation [20,21] and total factor productivity [22,23], thereby enhancing the ability of the financial sector to serve the real economy and facilitating the high-quality development of the economy.…”
Section: Introductionmentioning
confidence: 99%
“…Many existing studies focus on the impact of fintech development on traditional financial institutions [11][12][13][14][15][16][17]. Emerging studies find that fintech has positive effects on corporate financing, innovation and efficiency [18][19][20][21][22][23]. Few papers study the impact of fintech development on corporate governance.…”
Section: Introductionmentioning
confidence: 99%